Die hedendaagse wêreldbeeld met toespitsing op Afrika - Osthuizen, G. C. (Koers, 1985)
The author takes issue immediately with the fact that contemporary world views are contrasted, as a matter of course, with Africa. He discusses in detail the development of the contact between Africa and the West, pointing out to what extent and in what ways Western ways of thought have infiltrated into the African psyche. Subsequently he deals with the modern and the post-modern view of the world, pointing out that the post-modern, with its radically new ways of thought (e.g. quantum physics) have implications for Africa as well. After a discussion of the views of the primal nations of Africa, and an evaluation of the sophistication of the cultures in contrast to the stereotyped view of their "primitiveness", he goes on to a discussion of their views of the divine, concluding with the idea that God is not voluntarily Deus Absconditus - God is formally distant, but existentially present.